The political economics of cancer drug discovery and pricing. Issue 12 (December 2020) - Taylor, David G.
Highlights: Despite falling age-specific mortality rates cancers are causing a rising proportion of all deaths. Anticancer medicines now cost 0.1−0.2% of the typical OECD country's GDP. Although complex, imperfect and politicised, markets for innovative medicines are delivering important benefits. Without risk sharing and value based pricing the IP laws facilitating much drug discovery may become politically unsustainable. Globally, equitable access to innovative cancer therapies demands differential (Ramsey) pricing. Abstract : Drug discoveries can, when used appropriately, save lives. Since 1970, cancer death rates among people aged under 65 have halved in countries such as the USA and the UK. Despite pharmaceutical market imperfections and fears about the prices of new treatments, further progress should be possible during the 2020s. Anticancer medicine outlays account for 0.1–0.2% of the gross domestic product (GDP) of developed countries. Total cancer service spending typically stands at ∼0.8% of GDP. The affordability of these sums is a political calculation. Improvements in the efficiency of drug development and global access to effective therapies are desirable. However, from a public interest perspective, these goals should not be pursued in ways that understate the value of better treatment outcomes and threaten the funding available for ongoing innovation. Teaser: In highly politicised and heavily regulated markets for new anticancer drugs, the long-term value of extending life and reducing illness-related distress and disability is at risk of being underestimated: the fundamental goal of pharmaceutical price regulation should be to help assure universal access to continuously improving treatment.